PENGARUH NILAI-NILAI AGAMA, KUALITAS LAYANAN, PROMOSI, DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENJADI NASABAH BANK SYARIAH DI BANJARMASIN - Rika Yulianti; Marijati Sangen; Ahmad Rifani (Universitas Lambung Mangkurat, 2016)
The purposes of this study are (1) to know and analyze the influence of religious values, quality of service, promotion, and trust simultaneously against the decision of becoming customer of Bank Syariah in Banjarmasin, (2) to find out and to analyze the influence of religious values against the decision of customer of Bank Syariah in Banjarmasin, (3) to identify and to analyze the effect of quality of service to customer of Bank Syaria decision in Banjarmasin, (4) determine and analyze the effect of promotions to decision of customer of Bank Syariah in Banjarmasin, (5) to determine and to analyze the effects of confidence in the decision of customer of Bank Syariah in Banjarmasin. This study used nonprobability sampling and purposive sampling techniques, by taking samples of 100 respondents who became customers of Bank BPD Kalsel Syariah, Bank Syariah Mandiri, Bank BRI Syariah and Bank BNI Syariah, of which 25 persons were taken of each bank as samples. This research was descriptive. The data were collected by distributing questionnaires, while data analysis method used was multiple linear regression. The results of research proved that religious values, quality of service, promotion, and beliefs had significant effects simultaneously against the decisions of the customers of Bank Syariah in Banjarmasin, religious values significantly influenced the decisions of the customers of Bank Syariah in Banjarmasin, service quality significantly influenced the decisions of the customers of Bank Syariah in Banjarmasin, promotions significantly affected on the decisions to become the customers of Bank Syariah in Banjarmasin, and trust significantly influenced the decisions of the customers of Bank Syariah in Banjarmasin